PERILAKU PERUNDUNGAN TERHADAP SISWA: URGENSI KOMPETENSI KEPRIBADIAN GURU PAI - Arliansyah Maulana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This research aims to understand the urgency of the personality competence of Islamic Education (PAI) teachers in preventing bullying behavior among students. The study utilizes library research, which relies on data obtained from libraries or other sources containing validated references and documents, rather than fieldwork. The findings indicate that the personality competence of PAI teachers is crucial in supporting the learning process and shaping students' character. This competence encompasses noble character, emotional stability, and the ability to serve as a role model. Government regulations emphasize that PAI teachers must embody traits that reflect Islamic values, including dedication and discipline in fulfilling their duties. A positive teacher personality can prevent bullying in schools by creating an inclusive and supportive environment. PAI teachers act as mediators, counselors, and guides in addressing bullying behavior while teaching moral values that emphasize empathy and tolerance. Through this approach, it is hoped that students can avoid bullying and develop emotional intelligence and good character.